(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Abstract - In this work, we have prepared the nanofluid contains de-ionized water + ethylene glycol + aluminium oxide at difereent concentration (weight %) by both ultrasonic and magnetic stirrer method seperately. Various experiments were carried out to determine the thermo-physical properties of nanofluid and comparison were made to evaluate the effectiveness of fluid preparation method.